Activated Carbon Adsorbents Derived from Agricultural Waste for Phenolic Pollutant Removal: A Review - Zulaicha, Annisaa Siti; Kiswandono, Agung Abadi; Buhani, Buhani; Suharso, Suharso; Nitti, Fidelis; Rinawati, Rinawati (Indonesian Journal of Chemistry, 2025)
The widespread discharge of phenol into the environment has posed a threat to the environment. Phenol waste in the aquatic environment is mainly due to its involvement in various industries such as the petrochemical, pharmaceutical, and wood product sectors. Recent studies have shown that industrial waste contains phenol in the concentration range of 2.8 to 6800 mg/L. The presence of phenol in water can cause bioaccumulation in aquatic organisms, thus posing a risk to the food chain and human health through the consumption of phenol-contaminated seafood. Long-term exposure of humans to phenol-contaminated water causes health problems such as anorexia, progressive weight loss, and liver disorders. This emphasizes the importance of addressing and reducing phenol contamination to safeguard human health. Various treatment methods have been applied, including filtration, reverse osmosis, and adsorption. Among these, adsorption is widely used due to its simplicity and cost-effectiveness, with activated carbon as the most commonly used adsorbent. This study comprehensively reviews previous studies on agricultural waste-based activated carbon (palm shell, candlenut, and rubber) for phenolic compound removal. It examines characterization data (BET, XRD, SEM-EDX, and FTIR) and adsorption performance, aiming to provide recommendations of the most promising biomass for developing efficient activated carbon.